2018
DOI: 10.1097/qai.0000000000001615
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Injection-Related Risk Behaviors After Emergency Implementation of a Syringe Services Program During an HIV Outbreak

Abstract: Analyses of an SSP program and in-depth qualitative interview data showed rapid reduction of injection-related HIV risk behaviors among PWID post-SSP implementation. Sterile syringe access as part of comprehensive HIV prevention is an important tool to control and prevent HIV outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
(28 reference statements)
0
35
0
Order By: Relevance
“…We also found that using syringes from a safe source was associated with lower injection risk and finding it difficult to access sterile syringes was associated with elevated injection risk. These findings underscore the importance of harm reduction programs in reducing injection risk by providing free access to sterile injection equipment, offering risk reduction counselling and providing referrals to health and social services [35–37]. Unfortunately, in February of 2013 the Global Fund for HIV, Tuberculosis and Malaria withdrew support for NEPs in Mexico due to their rising gross domestic product [38].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that using syringes from a safe source was associated with lower injection risk and finding it difficult to access sterile syringes was associated with elevated injection risk. These findings underscore the importance of harm reduction programs in reducing injection risk by providing free access to sterile injection equipment, offering risk reduction counselling and providing referrals to health and social services [35–37]. Unfortunately, in February of 2013 the Global Fund for HIV, Tuberculosis and Malaria withdrew support for NEPs in Mexico due to their rising gross domestic product [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, a state US law prohibiting non-medical use of needles (a felony punishable by up to 3 years in prison) was suspended during the 2015 HIV outbreak in Scott County, Indiana, which contributed to significantly decreased injection risk behaviours. 17,69 The restrictive needle and syringe programme policy in Scott County delayed the implementation of an effective HIV prevention strategy until after an outbreak had already occurred. Temporary suspension of the ban is an admission that policy makers recognised the effectiveness of needle and syringe programmes, but the unwillingness to fund these programmes as a prevention strategy reaffirms misconceptions and stigma.…”
Section: Policy Environment Interventionsmentioning
confidence: 99%
“…9 In a recent article, researchers from ISDH, Indiana University, the Scott County Health Department and CDC suggest that “proactive establishment of SSPs in nonurban communities with PWID might help to prevent future outbreaks of HIV”. 12 In response to claims that the outbreak would have been prevented had a SEP been implemented earlier, Jerome Adams, Indiana State Health Commissioner at the time, pointed to evidence that many cities with active SEP also have high HIV prevalence: “My colleagues and I will never know — though HIV infection remains rampant in many urban areas that have needle-exchange programs”. 13…”
Section: Introductionmentioning
confidence: 99%